7 Quantifying the bio-distribution of transplanted HESC-ECS in a murine model of HLI by QPCR. (1st April 1997) - Fleisinger, Lucija; MacAskill, Mark G; Mountford, Joanne C; Baker, Andrew H; Newby, David E; Hadoke, Patrick WF
Abstract : Introduction: Beneficial effects of stem/progenitor cell therapies for the treatment of ischaemic diseases have been established; however, there remains conflicting evidence on whether cells act by incorporation into the existing vasculature or by paracrine effects. Objective: This study aims to quantify the bio-distribution of transplanted, proangiogenic, human embryonic stem cell-derived endothelial cells (hESC-ECs) in a murine model of hind limb ischaemia over 21 days using qPCR-detection of human DNA. Methods: CD1 nude mice (male, 6–8 weeks old; n=6 per group) underwent femoral artery ligation followed by injection with hESC-ECs into ischaemic muscle of the hindlimb. Mice were sacrificed at 0 hour, 4 hour, 24 hour, 7d, 14d, and 21d post-transplantation, and DNA extracted from the hind limb. A paired-qPCR assay was run with a set of human-specific and mouse-specific primers to allow for detection of hESC-ECs in mouse tissue. Results: A standard curve was constructed using mixtures of DNA extracted from mouse tissue and a population of hESC-ECs. The mean percentage of human cells at each time-point was determined accordingly. At the first time-point (0 hour), 1.77%±0.55% human cells were present within the ischaemic limb, with no significant change at 4 hour post-injection. However, by 24 hour and 7 days post-injection, the% human cells present significantly decreased to 0.67%±0.24% (p=0.05) and 0.35%±0.09% (p=0.05) respectively. At 14 and 21 days post-injection, the level of human DNA present had decreased to background levels. Conclusion: Our results suggest the majority of injected hESC-EC cleared from the injection site within the first 24 hours, with the remainder of the cells no longer present at 14 days post-injection. This is consistent with imaging data obtained prior to this study, and suggests that injected hESC-ECs improve perfusion in the mouse ischaemic limb by a paracrine mechanism rather than direct incorporation into the existing vasculature.